P195 On the effect of tdcs on risk taking behaviour: A study using the balloons analogue risk task. Issue 3 (March 2017) - Russo, R.; Wallace, D.; Twyman, P.; Cooper, N.; Fitzgerald, P.
Abstract : Introduction and Objectives: Fecteau et al. (2007) used the Balloon Analogue Risk Task (BART) in a transcranial direct current stimulation (tDCS) study to assess the extent to which the modulation of the activity of the dorsolateral prefrontal cortex (DLPFC) affects risk taking behaviour. Three separate bilaterally stimulated groups (right anodal/left cathodal; left anodal/right cathodal and sham) were tested under double-blind conditions with the electrodes placed over the DLPFC. They found that in both active stimulation groups (right anodal/left cathodal; left anodal/right cathodal), compared to sham, upregulating the DLPFC diminished risk-taking behaviour. In a second experiment using unilateral stimulation conditions where only right or left anodal stimulation was administered (referent electrode over the contralateral supraorbital region), no significant effect. They concluded that increasing activity in the DLPFC led participants to become more risk-averse. There are some potential caveats regarding their findings: primarily the study lacked in statistical power (total n = 35). Methods: To address the above issue we tried to replicate Fecteau et al. results closely mimicking their procedure while increasing the number of people tested (over 200 participants in 2 experiments). Results and conclusions: Overall, we could not replicate Fecteau et al.'s results. In one neuromodulation condition (right anodal/left cathodal), contrary to Fecteau et al. results, risk taking increased, however a closer look to the data suggests that this increase is more apparent than real.